Religious Moderation as Frameworl of Religious Tolerance in Rama Agung Argamakmur Village, Bengkulu Province - Kusuma, Wira Hadi; Supian, Aan; Ramdani, Rahmat; Astapala, Sultan Gholand; Hawasi, Hawasi; Syabibi, M. Ridho (Mimbar Agama Budaya, 2025)
This study examines how religious moderation becomes a mediator for society in a harmonious, tolerant life in Rama Agung Village, Argamakmur Regency, Bengkulu Province, where this study uses a qualitative approach where this technique is a strategy for collecting various information by understanding and focusing on hypotheses from different writings. Information gathering is done by searching and updating information from multiple sources, such as scientific journals, articles, and books on religious moderation. The study results show that Rama Agung Village has a very high tolerance attitude, which is indicated by the existence of harmonious coexistence between religious communities and community harmony that respects and supports each other. In addition, each spiritual leader is the bridge that allows their followers to carry out further religious activities. The interactions and actions of the residents of Rama Agung Village show openness and the ability to live side by side peacefully